IDENTIFICATION OF THE CONTRAST FULL VOWELSCHWA: TRAINING EFFECTS AND GENERALIZATION TO A NEW PERCEPTUAL CONTEXT - Esther Gómez Lacabex (Ilha do Desterro: A Journal of English Language, Literatures in English and Cultural Studies, 2008)
This study examines the ability to identify the English phonological contrast full vowel-schwa by Spanish learners of English after two different types of training: auditory and articulatory. Perceptual performance was measured in isolated words in order to investigate the effect of training and in sentences to study the robustness of acquisition in generalizing to a context which was not used during training. Subjects were divided into three groups: two experimental groups, one undergoing perceptual training and one undergoing production based training, and a control group. Both experimental groups’ perception of the reduced vowel improved significantly after training. Results indicated that students were able to generalize their reduced vowel identification abilities to the new context. The control group did not show any significant improvement. Our findings agree with studies that have demonstrated positive effects of phonetic training (Derwing. Munro & Wiebe, 1998; Rochet, 1995; Cenoz & García Lecumberri, 1995, 1999). Interestingly, the results also support the facilitating view between perception and production since production training proved beneficial in the development of perceptual abilities (Catford & Pisoni, 1970; Mathews, 1997). Finally, our data showed that training resulted in robust learning, since students were able generalize their improved perceptual abilities to a new context.